Analisis Keandalan Sistem Proteksi Pada Distribusi Tenaga Listrik 20 KV Di PT Karya Wisesa - Bernaldo Alonso; Muhammad Erpandi Dalimunthe; Haris Gunawan (Jurnal Nasional Teknologi Komputer, 2026)
The protection system is a crucial component in maintaining the reliability of the electric power distribution system, particularly the 20 kV medium-voltage network, which is vulnerable to various types of disturbances. This study aims to analyze the reliability of the protection system in the 20 kV electric power distribution network at PT Karya Wisesa through evaluation of Over Current Relay (OCR) and Ground Fault Relay (GFR) settings, short-circuit current analysis, and protection coordination. The research method involved system data collection, load calculations, fault current analysis, and relay coordination evaluation based on protection operation time and selectivity. The results showed that the protection system had a sensitivity of 21.44, a main relay operation time of 0.28 seconds, and a Reliability Index of 95%. After optimizing the relay settings, the grading time increased from 0.17 seconds to 0.35 seconds, thus meeting the IEC 60255 standard. These results indicate that PT Karya Wisesa's 20 kV distribution protection system has a good level of reliability in selectively detecting and isolating disturbances.